2016
DOI: 10.5667/tang.2016.0015
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of Taemyeongcheong on allergic reactions

Abstract: Taemyeongcheong (TMC) is Korean traditional extracted drink with various health ingredients. TMC has been used to treat hepatic damage, obesity, gastritis, and colitis. However, the role of TMC on allergic reaction has not been studied yet. In this study, we investigated the anti-allergic effects of TMC against a compound 48/80-induced systemic anaphylactic reaction and IgE-mediated passive cutaneous anaphylaxis (PCA). TMC significantly inhibited the compound 48/80-induced systemic anaphylactic reaction and Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Taemyeongcheong (TMC) is a health functional beverage made using traditional methods in Korea, and it is commonly found in various foods and herbal ingredients. TMC inhibits the allergic effects induced by 48/80 [21] and acetaminophen-induced hepatic damage in vivo [22]. We already reported that TMC inhibited Th2 cytokines such as IL-1β, IL-6, and IL-10 as well as iNOS and COX-2 in LPS-induced RAW 264.7 cells [23].…”
Section: Introductionmentioning
confidence: 97%
“…Taemyeongcheong (TMC) is a health functional beverage made using traditional methods in Korea, and it is commonly found in various foods and herbal ingredients. TMC inhibits the allergic effects induced by 48/80 [21] and acetaminophen-induced hepatic damage in vivo [22]. We already reported that TMC inhibited Th2 cytokines such as IL-1β, IL-6, and IL-10 as well as iNOS and COX-2 in LPS-induced RAW 264.7 cells [23].…”
Section: Introductionmentioning
confidence: 97%
“…Taemyeongcheong (TMC) is a health functional beverage made using traditional methods in Korea, and is commonly found in various foods and herbal ingredients. TMC inhibits the allergic effects induced by 48/80 (22) and acetaminophen-induced hepatic damage in vivo (23). We have previously reported that TMC inhibited Th2 cytokines such as IL-1β, IL-6, and IL-10 as well as iNOS and COX-2 in LPS-induced RAW 264.7 cells (24).…”
Section: Introductionmentioning
confidence: 99%